2020
DOI: 10.1037/cns0000256
|View full text |Cite
|
Sign up to set email alerts
|

Conscious thought during the resting state in patients with severe health anxiety and patients with obsessive–compulsive disorder.

Abstract: The resting state is a commonly used paradigm in neuroimaging studies that has demonstrated differences in functional connectivity during rest in anxiety disorders, compared to healthy controls. Surprisingly, the psychological aspects (e.g., thoughts, feelings) during the resting state have largely been ignored in clinical populations, while increasingly studied in healthy populations. To the knowledge of the authors, this is the first study to examine the cognitive and affective experiences of resting state c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
(94 reference statements)
0
4
0
Order By: Relevance
“…One must feel comfortable to maintain focus of attention, including to own thoughts as reflected in the strong negative correlations between Discontinuity of Mind and Comfort (Diaz et al, 2013). Several studies using the ARSQ have reported reduced Comfort in clinical cohorts, including insomnia (Palagini et al, 2016), autism (Simpraga et al, 2021), and also health anxiety and obsessive compulsive disorder (Gehrt et al, 2020). Thus, there is a need and our results indicate a potential for MBSR to facilitate a greater feeling of comfort in these disorders.…”
Section: Does General Well-being Drive Our Thoughts and Feelings In Every Moment?mentioning
confidence: 71%
See 1 more Smart Citation
“…One must feel comfortable to maintain focus of attention, including to own thoughts as reflected in the strong negative correlations between Discontinuity of Mind and Comfort (Diaz et al, 2013). Several studies using the ARSQ have reported reduced Comfort in clinical cohorts, including insomnia (Palagini et al, 2016), autism (Simpraga et al, 2021), and also health anxiety and obsessive compulsive disorder (Gehrt et al, 2020). Thus, there is a need and our results indicate a potential for MBSR to facilitate a greater feeling of comfort in these disorders.…”
Section: Does General Well-being Drive Our Thoughts and Feelings In Every Moment?mentioning
confidence: 71%
“…Using the ARSQ, reproducible patterns of individual thoughts and feelings have been observed, and associated with scores on insomnia, anxiety, and depression in large population samples (Diaz et al, 2013). Likewise, mental disorders including health anxiety, obsessive compulsive disorder (Gehrt et al, 2020) insomnia disorder (Palagini et al, 2016) and autism spectrum disorder (Simpraga et al, 2021) have been associated with distinct ARSQ profiles. Studies of the therapeutic benefits of MBSR have used clinical scales that refer to experiences during weeks or even months to assess participants' well-being, as well as symptoms of stress, anxiety, and depression.…”
Section: Introductionmentioning
confidence: 97%
“…The study was reviewed by the ethics committee at the Center on Autobiographical Memory Research, Aarhus University, Denmark. The main measures presented in this article are nonoverlapping with previous publications from this study Gehrt, Frostholm, Pallesen, et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…All participants agreed to an informed consent form explaining the nature of the study, as well as issues relating to confidentiality and withdrawal. The main measures presented in this article are non‐overlapping with previous publications from this study (Gehrt, Frostholm, Obermann & Berntsen, 2020a; Gehrt, Frostholm, Pallesen et al ., 2020b; Gehrt et al ., 2022). 2…”
Section: Methodsmentioning
confidence: 99%